(untitled) (Journal of EAHIL, 2017)
This article describes the approach used by the Bibliosan 2.0 team (in a project funded by the Italian Ministry of Health) in developing the Bibliosan 2.0 website (http://bibliosan20.wordpress.com/) aimed at offering guidance and advice to our users for the use of Web 2.0 tools and technologies. To complement the website, we decided to deliver filtered information through Web 2.0 tools such as our blog, Twitter, Delicious and Zotero. To do so, we adopted a very targeted, strategic approach in selecting which tools to present, keeping in mind that our audience is made up of librarians, researchers and health professionals.